2010
DOI: 10.1007/s11664-010-1380-4
|View full text |Cite
|
Sign up to set email alerts
|

Crack Development in a Low-Stress PBGA Package due to Continuous Recrystallization Leading to Formation of Orientations with [001] Parallel to the Interface

Abstract: Thermal cycling was imposed on plastic ball grid array (PBGA) packages with a small die, a package design that does not impose a large strain on solder joints. Less cracking was observed after 2500 cycles from 0°C to 100°C (with 10 min dwell times and 10 min ramps) than in a prior study with a higherstress package design, so these samples were thermally cycled (TC) to 6400 cycles to investigate the relationship between cracks, microstructure, and grain crystal orientation. Cracked joint locations within the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…The results showed that the evolution of microstructures in the strain concentration regions commenced with gradual evolution of the cellular solidification structure, but after some time, i.e., the incubation period, the microstructures changed discontinuously by recrystallization. A similar observation has been reported in [66].…”
Section: The Role Of Recovery and Recrystallization In The Failure Mesupporting
confidence: 90%
“…The results showed that the evolution of microstructures in the strain concentration regions commenced with gradual evolution of the cellular solidification structure, but after some time, i.e., the incubation period, the microstructures changed discontinuously by recrystallization. A similar observation has been reported in [66].…”
Section: The Role Of Recovery and Recrystallization In The Failure Mesupporting
confidence: 90%
“…However, nucleation of a new grain is only stable if the misorientations are large enough, so high-angle grain boundaries must occur abruptly. 26 In contrast, continuous recrystallization is a recoverydominated process leading to ongoing increases in boundary misorientation and conversion of lowangle boundaries into high-angle ones by coalescence and rotation.…”
Section: Recrystallizationmentioning
confidence: 99%
“…27 This would tend to favor continuous, rather than discontinuous, recrystallization. 26 Also, the misorientation of the Ag 3 Sn precipitates is by nature high. Indeed, detailed studies have shown thermal cycling of SnAgCu joints to first lead to the formation of new subgrains within the individual b-Sn dendrites 12 ), and eventually between the densely spaced precipitates as well, after which these subgrains then continue to rotate during ongoing cycling.…”
Section: Recrystallizationmentioning
confidence: 99%
See 2 more Smart Citations